2019
DOI: 10.1093/jee/toz057
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and behavioral responses of Bradysia odoriphaga (Diptera: Sciaridae) to volatiles from its Host Plant, Chinese Chives (Allium tuberosum Rottler ex Spreng)

Abstract: Bradysia odoriphaga Yang et Zhang is a serious belowground pest of Chinese chives (Allium tuberosum). Our previous studies have indicated that B. odoriphaga females prefer to oviposit near the roots of Chinese chives rather than the roots of other plants, and that the performance (longevity and fecundity) of B. odoriphaga offspring was better on Chinese chives than on Lettuce (var. ramosa Hort.), Onion (Allium cepa) and Potato (Solanum tuberosum) but little is known about how the volatiles released by Chinese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…lucorum ; Bradysia odoriphaga produced strong electrophysiological and behavioural responses to some disulphides (Yang et al, 2019 In this study, both A. suturalis and A. lucorum showed olfactory preference to this mixed attractant suggesting the similarity of olfactory response between the two species of mirid bugs (Wang et al, 2018).…”
Section: Ta B L E 1 Attractive Effects Of Six Plant Extracts On Apolysupporting
confidence: 48%
See 1 more Smart Citation
“…lucorum ; Bradysia odoriphaga produced strong electrophysiological and behavioural responses to some disulphides (Yang et al, 2019 In this study, both A. suturalis and A. lucorum showed olfactory preference to this mixed attractant suggesting the similarity of olfactory response between the two species of mirid bugs (Wang et al, 2018).…”
Section: Ta B L E 1 Attractive Effects Of Six Plant Extracts On Apolysupporting
confidence: 48%
“…Previous studies have reported that insects showed same response to the compounds with similar structures. For example, many butyl esters play an important role in host localization of A. lucorum (Pan, et al., 2015); Bradysia odoriphaga produced strong electrophysiological and behavioural responses to some disulphides (Yang et al., 2019). In the volatiles of Chaenomeles speciosa and Jinmudan Oolong tea which were important host plants of A. lucorum , many kinds of phthalate esters were identified (Wang and Kang, 2010; Xu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…AT antitumor activity could depend on substances found in Allium genus, just like organosulfur compounds: methyl allyl disulfide and diallyl disulfide [20]. These organosulfur molecules have immune stimulant effects, which could be responsible of anticancer effects of these molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the insect pheromones 4-methyl-3,5-heptanedione and (E8, E10)-dodecadienol have been used as attractants for Sitona lineatus [11] and Cydia pomonella [15]. In our previous study, we have shown that the volatiles methyl allyl disulfide and diallyl disulfide, emitted from Chinese chives, could regulate host location and oviposition behavior in B. odoriphaga adults [16]. In another study, the sex pheromone nheptadecane could regulate the behavior of B. odoriphaga male adults [17].…”
Section: Introductionmentioning
confidence: 99%